COMPARISON BETWEEN SOLAR THERMAL-POWERED ABSORPTION REFRIGERATION CYCLE AND PHOTOVOLTAIC-POWERED COOLING TECHNOLOGIES APPLIED TO DATA CENTERs - Belizário, A.; Simões-Moreira, J. R. (Revista de Engenharia Térmica, 2022)
The air conditioning system of a Data Center is a great challenge for mechanical engineers. At the same time, it is fundamental for computer safety, it is a great energy consumer. Considering that, the present work carried out an analysis in which a solar-powered absorption refrigeration cycle system is combined with a conventional electrical chiller system. The proposed system also introduces the use of PV panels to generate electricity to power the electric chiller. A decision algorithm was developed based on local solar parametric data and cooling demand. A case study was analyzed for a typical data center located in the city of São Paulo, Brazil. Electrical specific installed power demands of 0.5, 1.0, 2.0, 4.0, and 8.0 kW/m² at half and total load were studied. Local solar irradiation and temperature indexes were based on the data obtained from ASHRAE [1]. The results show that, for a typical year, the absorption solar system performs better than the photovoltaic system in most cases (0.5, 1.0, 4.0, and 8.0 kW/m²), except when the baseline of the installation operates near the optimum point of the consumption curve of the chiller, which occurs at 2 kW/m². Finally, the study shows that air conditioning systems powered by solar energy are a great alternative to reduce the energy consumption and operational costs of a Data Center.